Assessment of fully digitalized workflow for implant-prosthetic rehabilitation in temporomandibular disorders patients: A clinical study - Giuseppe Minervini; Rocco Franco; Salvatore Crimi; Manuele Basili; Saurabh Chaturvedi; Marco Cicciù; Alberto Bianchi; Gabriele Cervino (Elsevier, 2023)
Digitalized workflow eliminates the need for the tray, impression materials, its decontamination, packaging and shipping, pouring with plaster, cast fabrication, mounting in an articulator, reducing storage spaces, and the risks of any loss or fracture of the plaster model is overcome by archiving on the computer. This clinical investigation aimed to evaluate the effectiveness of the fully digitalized rehabilitation [implant-supported prosthesis] method in partially edentulous patients and with TMD, using advanced software. Twelve patients requiring implant-supported prosthesis in the mandibular molar area with Temporomandibular disorders [TMD] were selected. The fully digitalized rehabilitation method with advanced software was used for rehabilitation. For each subject, Optical impressions, CBCT scan, and Digital recording of jaw movement data. Guided implant surgery and digitalized prosthetic rehabilitation; were performed. The effectiveness of the digitalized workflow was assessed by evaluating the changes in the joint symptoms before and after the end of the treatment, changes in the electromyographic tracings, the precision of the prosthetic artefact, assessed through the amount of chair adjustment operating time and the number of retouching/ modifications to be carried out before the completion of the work. The results showed that the mean operative time required in 12 patients was 9.42 min, significantly less than the time recorded in previous studies when the medium mean was 16.00 min. The mean number of touch-ups [adjustments] was less than 3, most of which were on the interproximal surfaces. There were no significant changes recorded in the electromyography tracings. There were also no changes in joint symptoms. It was found that this way of working was entirely reliable and significantly reduced operating times and the number of appointments. Digital flow is beneficial ei dysfunctional patients, not about improvements in temporomandibular symptoms but in times of operability and prosthetic retouching.